Pemberdayaan Masyarakat Dalam Skrining Perdarahan Antepartum dan Post Partum di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Nurdiana Manurung; Dwi Ris Hasanah S (Journal of Community Development, 2022)
Antepartum Hemorrhage and Postpartum Hemorrhage are signs that indicate a danger that can occur during pregnancy or the antenatal period. This is very necessary for pregnant women to know, especially those that threaten the safety of the mother and the fetus in her womb, at least what pregnant women should know to recognize Antepartum Hemorrhage and Postpartum Hemorrhage, such as bleeding, reduced fetal movement, abdominal pain and severe headaches (Carlos et al., 2020). Early detection of risk factors is needed to reduce mortality and morbidity of mothers and their fetuses. This is where the role of health workers in early detection of danger signs. This study aims to improve the ability of health cadres to detect early and refer cases of high-risk pregnancy, childbirth and postpartum. The research method used analytic research. Early detection of antepartum hemorrhage and postpartum hemorrhage by the family and recognition of risk factors and complications, as well as appropriate treatment by health workers is the best way to reduce MMR and IMR. The targets of this activity were health cadres and pregnant women, 30 respondents were obtained in Kelurahan Baru Ladang Bambu, Medan Tuntungan Subdistrict. The interventions carried out in this activity were counseling, discussion, and simulation. The measuring instrument used pretest and posttest questionnaires. Data were analyzed using Wilcoxon test analysis. The results of the activity are an increase in the knowledge of cadres and pregnant women about the detection of danger signs of pregnancy, antenatal services provided can obtain data on the condition of their pregnancy and become information for pregnant women until now is still high.